Pelatihan Manajemen Keuangan Bagi Pelaku Usaha Batu Bata di Kelurahan Silandit - Silviana Batubara; Makhrani; Ade Maya Mei Shanty; Emirza Henderlan HARAHAP (Jurnal Transformasi Pendidikan Indonesia, 2025)
This study aims to explore the effectiveness of financial management training for brick industry entrepreneurs in Silandit Village. The training is designed to enhance entrepreneurs' understanding and skills in managing their business finances, including transaction recording, budget planning, and cash flow management. The results show that before the training, most entrepreneurs lacked an organized record-keeping system and struggled to create effective budget plans. After attending the training, 75% of participants started recording their financial transactions regularly, while 85% successfully developed more structured monthly budgets. Entrepreneurs also demonstrated improvements in managing cash flow and expenses. However, challenges in maintaining consistency in applying the learned financial management practices remain, requiring ongoing support. Overall, the training has had a positive impact on the financial management of brick entrepreneurs in Silandit Village and is expected to support the sustainability and growth of their businesses.